Design of photovoltaic-thermal (PVT) platform - Cheng, Wei Yang (Nanyang Technological University, 2022)
One of the alternative sources of sustainable energy is solar energy, where the photons from the sunlight are harvest and converted into the electrical energy for consumption. As at any point in time, half of the world is facing the sun, this vastly increases the potential of solar energy to be adopted worldwide when comparing to other alternatives such as hydroelectric. Typically, the solar panels run at lower than 20% efficiency under most conditions. However, as not all photons in the sunlight are absorbed and converted into electrical energy, those that are not, -are retained as heat. This results in increased temperature of the solar panel leading to fall in light to electric efficiency. Hence, in countries that experiences winter conditions, a solar thermal collector is placed behind the solar panel to absorb the heat for central heating or domestic hot water as part of the intended design. However, this has not been applied on a large-scale in Singapore and most solar installations are just stand-alone solar panels with no thermal collector to absorb the heat. Hence the objective of this project is to design and study a thermal collector to deploy existing solar installations so as to improve the efficiency of the entire system. After which, Computer simulation studies-using commercially available software computational code ANSYS FLUENT will be carried out to investigate the effectiveness of the said design. One potential application of the design would be used in the many solar panels currently installed on the roof top in Singapore. The results show that the thermal collector designs are able to cool the solar panels to varying degrees without adversely affecting solar panel operation. It is possible to harness the heat in the thermal collector for domestic hot water use. A further step is to validate the simulation results with actual physical experimental data through a small scale prototype.